Acid lime (Citrus aurantifolia) production as influenced by different fertigation levels with irrigation schedules - PAWAR, P S; SHIRGURE, P S; JAGTAP, D D; PATIL, PRAKASH (The Indian Journal of Agricultural Sciences, 2020)
The sustainable production of acid lime is possible with combined use of irrigation water with fertilizer through micro-irrigation. The integrated use of drip irrigation with fertigation on yield, quality and economy of 14 year-old acid lime (Citrus aurantifolia Swingle) cv. Sai-Sharbati was studied during 2011–16 at Mahatma Phule Krishi Vidyapeeth, AICRP on Fruits, Rahuri (M.S.). The study was undertaken on the black soil with the base recommended dose of fertilizers (RDF) as 600:200:600 (N:P2O5:K2O). The experiment was in Factorial Randomised Block Design with nine treatments, comprising three irrigation schedules, viz.70% evaporation replenishment (ER) (I1), 80% ER (I2), and 90% of ER (I3), and three fertigation levels, viz. fertigation with 60 % RDF (recommended dose of fertilizers) (F1), 70% RDF (F2) and 80% RDF (F3) based NPK doses replicated six times. The highest canopy and fruit yield of acid lime was observed with the irrigation schedule at 90% ER with 80% RDF fertigation followed by 70% RDF fertigation. The highest yield efficiency (5.05 kg/m3) was also with irrigation schedule at 80% and 60% RDF fertigation. However the highest partial factor productivity of nutrients (66.12 kg fruit/kg NPK) and higher B/C ratio (1.95) was obtained with irrigation at 90% ER and with 60% RDF fertigation and by 90% ER with 80% RDF respectively. The quality production of acid lime fruits was obtained with irrigation schedule at 90% ER with 80% RDF fertigation.